Youth Associations and Entrepreneurship: Insights from Case Studies in Portugal - António, Nuno (2022)
The development of skills for entrepreneurship among young people has attracted interest at various levels, as a way of overcoming many problems that affect this group in the areas of economic development and job creation. This article assumes that participating in a youth association enables young people to develop a series of skills, in particular, their entrepreneurial capacities. This study pays attention to the contributions of the participation in youth associations for the promotion of entrepreneurship. The investigation based on a qualitative approach, through comparative case studies in Portugal. It was possible to verify that youth associations assume a dual role, on the one hand contributing to the personal, social and professional development of its leaders, members and participants, and on the other hand, as a promoter of social transformation, particularly at the local level.